2013
DOI: 10.4049/jimmunol.1201630
|View full text |Cite
|
Sign up to set email alerts
|

TRIF-Mediated TLR3 and TLR4 Signaling Is Negatively Regulated by ADAM15

Abstract: TLRs are a group of pattern-recognition receptors that play a crucial role in danger recognition and induction of the innate immune response against bacterial and viral infections. The TLR adaptor molecule, Toll/IL-1R domain-containing adaptor inducing IFN (TRIF), facilitates TLR3 and TLR4 signaling and concomitant activation of the transcription factors, NF-κB and IFN regulatory factor 3, leading to proinflammatory cytokine production. Whereas numerous studies have been undertaken toward understanding the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…In colonic SEMFs, the TLR-3 ligand [poly(I:C)] stimulated LL-37 expression. Previous studies reported that the TLR adaptor molecule (TRIF) facilitates TLR-3 signalling and concomitant activation of the transcription factors, NF-jB and AP-1, leading to proinflammatory cytokine production [28,36]. In this study, we demonstrated for the first time that the TLR-3-mediated intracellular signalling pathway leading to LL-37 expression required the formation of a complex of adaptor proteins, TRIF, TRAF6 and TAK1 in human colonic SEMFs.…”
Section: Ll-37 Expression In Ibdmentioning
confidence: 58%
“…In colonic SEMFs, the TLR-3 ligand [poly(I:C)] stimulated LL-37 expression. Previous studies reported that the TLR adaptor molecule (TRIF) facilitates TLR-3 signalling and concomitant activation of the transcription factors, NF-jB and AP-1, leading to proinflammatory cytokine production [28,36]. In this study, we demonstrated for the first time that the TLR-3-mediated intracellular signalling pathway leading to LL-37 expression required the formation of a complex of adaptor proteins, TRIF, TRAF6 and TAK1 in human colonic SEMFs.…”
Section: Ll-37 Expression In Ibdmentioning
confidence: 58%
“…The Flag-TRIF was as described [17]. The plasmids pcDNA3: MyD88-cmyc, Flag-TRAM and TRAM-G2A were generously provided by Professor Luke O’Neill (Trinity College Dublin).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, more recent progress in the biology of the IFN system points to epigenetic modulations as another component of IFN-induced innate immune response, suggesting the existence of a not yet fully explored “epigenetic signature” in genes activated by IFNs [124,125,126]. …”
Section: Type I Ifn Signaturementioning
confidence: 99%